2003
DOI: 10.1021/jp030403w
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared and Raman Spectroscopic Study of Chromatographically Isolated Li@C60 and Li@C70

Abstract: IR and Raman investigations have been carried out on purified Li@C60 and Li@C70 produced by low-energy ion implantation. The structural interpretations, based on theoretical considerations and comparison of the obtained vibrational spectra with those of different known fullerene oligomers, have shown that neither of the chromatographically isolated endohedral species (Li@C60(70)) correspond to monomeric nonderivatized molecules. We ascribe the two different fractions of Li@C60 to a double-bonded dimer and a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…5,6 Early experiments on the isolated material showed the considerably higher reactivity compared to C 60 with a tendency for the purified material to oligomerise. 7 Thin films were shown to exhibit metallic conductivity if kept under high vacuum conditions. 8 More recently, the production of Li@C 60 has been upscaled and commercialised by using a related plasma implantation technique.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Early experiments on the isolated material showed the considerably higher reactivity compared to C 60 with a tendency for the purified material to oligomerise. 7 Thin films were shown to exhibit metallic conductivity if kept under high vacuum conditions. 8 More recently, the production of Li@C 60 has been upscaled and commercialised by using a related plasma implantation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Early theoretical work focussed on the prediction of infrared and Raman [53,54] and neutron scattering [49] spectra due to the motion of X = He, Li + , Na + , K + and CO inside the near-spherical C 60 cage. The predictions of [53] were subsequently confirmed experimentally [55,56] for the infrared bands of Li + @C 60 . Confirmation of the predicted Raman bands [53] of Li + @C 60 is tentative [56].…”
Section: He Atom Inside C 70 Cagementioning
confidence: 60%
“…The predictions of [53] were subsequently confirmed experimentally [55,56] for the infrared bands of Li + @C 60 . Confirmation of the predicted Raman bands [53] of Li + @C 60 is tentative [56]. Later the theoretical studies were extended to study the dynamics and spectra of atoms, molecules and ions trapped in nonspherical cages, e.g.…”
Section: He Atom Inside C 70 Cagementioning
confidence: 60%
“…[28] As the interactions of lithium with both SWCNTs and the fullerenes inside the nanotubes are strong due to the small ionic radius and the special properties of the lithiumÀcarbon bond, [10,29] they could be similar to those in fullerenes prepared by the bombardment of C 60 by lithium. [29] In situ spectroelectrochemistry: The Raman spectra of lithium-doped peapods after water treatment indicated residual doping. For potassium-doped peapods it has been shown that it is possible to "de-dope" a sample by applying anodic electrochemical charging.…”
Section: Resultsmentioning
confidence: 99%